2023
DOI: 10.1111/cas.15745
|View full text |Cite
|
Sign up to set email alerts
|

HNRNPC suppresses tumor immune microenvironment by activating Treg cells promoting the progression of prostate cancer

Abstract: Immune microenvironment could affect the biological progress in prostate cancer (PCa) through N6 methyl adenosine (m6A) methylation. The purpose of this study was to investigate the crosstalk between m6A methylation and immune microenvironment and explore potential biomarkers to improve the immunotherapeutic response. Firstly, according to 11 differentially expressed m6A genes between normal and tumor samples, PCa patients were divided into immune microenvironment subtype 1 (IMS1) and IMS2 based on m6A gene pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Increasing studies have revealed the m 6 A regulatory patterns of PCa and correlated these modification patterns with the tumor immune cell infiltration microenvironment characteristics ( 49 51 ). In addition, a recent paper found that m 6 A reader HNRNPC can regulate Treg cell abundance as a possible mechanism for m 6 A methylation-mediated response against CTLA-4, indicating that activation of the immune microenvironment by targeting m 6 A regulators may serve as a potential therapeutic approach for advanced PCa( 52 ).Our study synthetically analyzed the relationship between the expression of m 6 A regulators and immune characteristics and drug sensitivity of PCa patients. In accordance with the previous reports, we confirmed that resting memory CD4+ T cells and Tregs are highly correlated with m 6 A-related genes ( 53 , 54 ), while both high- and low-risk groups are sensitive to a number of therapeutic drugs.…”
Section: Discussionmentioning
confidence: 92%
“…Increasing studies have revealed the m 6 A regulatory patterns of PCa and correlated these modification patterns with the tumor immune cell infiltration microenvironment characteristics ( 49 51 ). In addition, a recent paper found that m 6 A reader HNRNPC can regulate Treg cell abundance as a possible mechanism for m 6 A methylation-mediated response against CTLA-4, indicating that activation of the immune microenvironment by targeting m 6 A regulators may serve as a potential therapeutic approach for advanced PCa( 52 ).Our study synthetically analyzed the relationship between the expression of m 6 A regulators and immune characteristics and drug sensitivity of PCa patients. In accordance with the previous reports, we confirmed that resting memory CD4+ T cells and Tregs are highly correlated with m 6 A-related genes ( 53 , 54 ), while both high- and low-risk groups are sensitive to a number of therapeutic drugs.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, a previous study demonstrated the correlation between m6A methylation and immune cell infiltration in PCa [33]. Another study has shown that HNRNPC may activate the immune-suppressive tumor microenvironment by promoting PCa progression [53]. Hence, it is noteworthy to study the therapeutic potential of targeting upstream m6A regulators to activate the immune microenvironment in PCa.…”
Section: Discussionmentioning
confidence: 99%
“…However, Li et al. reported that HNRNPC regulated the activation of Treg cells by activating the immune microenvironment, which may be a potential therapeutic target for prostate cancer ( 35 ). In pancreatic cancer, HNRNPC induced DNA damage repair and cancer-associated fibroblast activation through the RhoA/ROCK2-YAP/TAZ signaling pathway ( 36 ).…”
Section: Discussionmentioning
confidence: 99%